Event Representation in Language and Cognition - Bohnemeyer, Jürgen; Pederson, Eric (Language, culture and cognition, 2010)
Event Representation in Language and Cognition examines new research into how the mind deals with the experience of events. Empirical research into the cognitive processes involved when people view events and talk about them is still a young field. The chapters by leading experts draw on data from the description of events in spoken and signed languages, first and second language acquisition, co-speech gesture and eye movements during language production, and from non-linguistic categorization and other tasks. The book highlights newly found evidence for how perception, thought, and language constrain each other in the experience of events. It will be of particular interest to linguists, psychologists, and philosophers, as well as to anyone interested in the representation and processing of events.
Title from publishers bibliographic system (viewed on 18 Feb 2013)
Keywords: Aufsatzsammlung; Wissensrepräsentation; Kognitive Linguistik